International Community Service: Teaching the Al-Qur'an and Islamic Values at Surau Wang Ulu, Perlis, Malaysia - Said, Ratna (Sasambo: Jurnal Abdimas (Journal of Community Service), 2026)
Kegiatan pengabdian masyarakat internasional ini bertujuan untuk melakukan pendampingan pembelajaran Al-Qur'an dan internalisasi nilai-nilai Islam bagi anak-anak rentan di Surau Wang Ulu, Perlis, Malaysia. Khalayak sasaran melibatkan 15 anak di sekitar daerah tersebut yang mengalami kerentanan keluarga dan keterbatasan ekonomi. Program ini dilaksanakan melalui metode talaqqi (pembelajaran tatap muka langsung), ceramah interaktif, dan pendampingan karakter harian. Kegiatan dilakukan dua kali seminggu, yaitu setiap hari Selasa dan Rabu setelah salat Magrib. Instrumen evaluasi yang digunakan adalah observasi klinis, lembar kontrol hafalan, dan refleksi partisipatif. Hasil menunjukkan adanya rata-rata kehadiran peserta mencapai 96,6% serta perubahan perilaku positif yang jelas berdasarkan observasi lapangan. Anak-anak menjadi lebih rajin mengikuti salat Magrib di surau secara konsisten. Selain itu, program bimbingan Al-Qur'an dirancang secara fleksibel sesuai dengan kemampuan membaca dan waktu yang tersedia bagi setiap anak, yang secara efektif menjaga motivasi mereka dalam belajar tanpa tekanan, serta berhasil meningkatkan skor keterampilan tajwid dasar, makhraj, kelancaran, dan hafalan surat-surat pendek mereka. Al-Quran Learning Assistance and Internalization of Islamic Values ​​for Vulnerable Children in Surau Wang Ulu, Perlis, Malaysia  This international community service activity aims to provide assistance in Al-Qur'an learning and the internalization of Islamic values for vulnerable children at Surau Wang Ulu, Perlis, Malaysia. The target audience involved 15 children in the surrounding area who experience family vulnerability and economic limitations. This program was implemented through the talaqqi method (direct face-to-face learning), interactive lectures, and daily character mentoring. The activities were conducted twice a week, specifically every Tuesday and Wednesday after Maghrib prayers. The evaluation instruments used were clinical observations, memorization control sheets, and participatory reflections. The results demonstrated an average participant attendance rate of 96.6% along with clear positive behavioral shifts based on field observations. The children became more diligent in consistently attending congregational Maghrib prayers at the surau. Furthermore, the Al-Qur'an mentoring program was designed flexibly according to each child's reading ability and available time, which effectively maintained their learning motivation without pressure, as well as successfully increased their scores in basic tajwid skills, makhraj, fluency, and short chapter memorization